2001
DOI: 10.1017/s0950268801006276
|View full text |Cite
|
Sign up to set email alerts
|

PCR–IMS detection and molecular typing of Cryptosporidium parvum recovered from a recreational river source and an associated mussel (Mytilus edulis) bed in Northern Ireland

Abstract: PCR-IMS was used to detect Cryptosporidium spp. in environmental water samples in Northern Ireland which had previously tested negative by a conventional IFA staining method. Oocysts of C. parvum detected in river water and final treated sewage effluent collected from various sites along the river Lagan were identified as genotype 2 (animal origin) based on polymorphisms observed at the thrombospondin related adhesion protein gene locus. Similarly, genotype 1 (human origin) oocysts of C. parvum were detected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 16 publications
3
29
0
1
Order By: Relevance
“…Up to 12.5 % of the samples analyzed contained Cryptosporidium oocysts. This rate is considerable high from a public health perspective and similar to those levels cited in previous reports (Gomez-Bautista et al, 2000;Lowery et al, 2001;Giangaspero et al, 2005). Moreover, water analysis in the area where the mussel samples were collected in the Chao Phraya River was also conducted.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Up to 12.5 % of the samples analyzed contained Cryptosporidium oocysts. This rate is considerable high from a public health perspective and similar to those levels cited in previous reports (Gomez-Bautista et al, 2000;Lowery et al, 2001;Giangaspero et al, 2005). Moreover, water analysis in the area where the mussel samples were collected in the Chao Phraya River was also conducted.…”
Section: Resultssupporting
confidence: 83%
“…In another study, infective C. parvum oocysts were detected in mussels and cockle from a shellfish-producing region that account for the majority of European shellfish production (Gomez-Bautista et al, 2000). All these data suggested that mussels and cockles could act as a reservoir of C. parvum infections to humans (GomezBautista et al, 2000;Graczyk et al, 1998;Graczyk et al, 2001;Lowery et al, 2001). In the present work, the green mussels (Perna viridis) native to the mouth of the Chao Phraya River have been examined for the presence of Cryptosporidium oocysts.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Mussels, clams, oysters, and cockles from several coastal regions have been confirmed as being naturally contaminated with Cryptosporidium oocysts (Fayer et al 1999;Lowery et al 2001;Giangaspero et al 2005;Li et al 2006). Oocysts of Cryptosporidium were also found in commercial shellfish from 64.9% of the sites examined along the Atlantic coast, either by microscopy using direct immunofluorescence assay or molecular testing.…”
Section: ; Gó Mez-couso Et Al 2005)mentioning
confidence: 99%
“…Reduction or elimination of PCR inhibitors prior to, during, or after DNA extraction has become an important stage in molecular diagnosis of protozoan pathogens in water and other environmental samples (Jiang et al, 2005). Currently, Cryptosporidium and Giardia by IMS and culture enrichment prior to DNA extraction are standard procedures to eliminate or considerably reduce substances that might be inhibitory to DNA amplification by PCR (Lowery et al, 2001;Nugent et al, 2001;Fontaine & Guillot, 2003). These, however, become impractical for organisms that have no IMS procedures or that cannot be cultured.…”
Section: Development In the Methods Of Detectionmentioning
confidence: 99%